A mão invisível no teto de vidro - Manganelli, Anelise (2012)
The aim of this study was to investigate the existence of the phenomenon also known as Glass Ceiling "Glass Ceiling". This phenomenon sets a limit on the invisible career, preventing women from ascending professionally. Can be empirically verified, that the earnings differential between men and women, has an acceleration to the final part of the distribution function of income, representing a barrier to the growth of income for women. The empirical strategy includes information about the household chores and occupations that may be useful to better understand the existence of this phenomenon in Brazil. For this purpose, we used information from the National Household Sampling (PNAD) for the year 2009 and the technique of quantile regression with correction of selection bias, which allows us to observe the impact of covariates on the income scale. The main results show evidence of the presence of the phenomenon of the "Glass Ceiling" in Brazil and demonstrate that the analysis of labor market should not separate the sphere of production, the sphere of reproduction, since the family, market and state are closely interwoven and are dependent.